Análisis de carbamato (BAYGON) en el ciclo de vida de Drosophila melanogaster (familia: Drosophilidae) (2017)
Drosophila melanogaster is the most used experimental model in genetic research for its short life cycle, rapid development, and reproduction, presenting advantages such as great offspring, economic cultivation and easy maintenance. The objective of this study was to analyze the possible alterations generated by the use of carbamate in the life cycle of Drosophila melanogaster. Banana culture media were made with 10 drops of nystatin and were fed to previously sterilized glass crystals in which a random mocha pair was introduced with three replicates for each volume used (0.3, 0.5 and 0.7 ml of carbamate) for 5 generations. Analysis of variance was performed under a randomized block model, the response variables analyzed were the duration of each stage (egg, larva, pupa, and adult) and the number of individuals killed or not passing to the next stage. The adults were observed in stereoscope and were made in the photographic registry, of the alterations such as: no hatching of eggs, decrease in larval size, alterations and little development in wings, change in pigmentation of omatids, prolongation of life cycle stages compared to control with p = 0.3809, treatment 0.7 had the highest mortality rate at all stages of the cycle.